ADJACENCY PAIRS AS UTTERED IN THE CONVERSATIONS OF SOFIA COPPOLA’S LOST IN TRANSLATION MOVIE SCRIPT - Heri Mudra (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2018)
This paper contains a discussion of the structures of Adjacency Pairs as uttered in the conversations of Lost in Translation movie script in terms of conversational analysis study. A conversation consists of at least two turns and two utterances which contain two acts of speech. Such utterances consisting of a first pair part which is followed by a second pair part form adjacent pairs which can be either preferred or dispreferred responses. Adjacency Pairs in term of preferred responses include twenty eight structures, while those in term of dispreferred responses include fourteen structures. The choice of a variety of responses is influenced by habits and cultures through which speakers convey meaning. Different habits and cultures of the speakers allow them to produce particular utterances which contain particular acts of speech. Subjectivity and intention influence the second speaker to respond the first speaker’s act based on what is intended. This is psychologically subjective rather than illogical. The complex structures of Adjacency Pairs are also caused by noises, unclear voices, and complex sentence patterns. The variations of adjacent pairs are basically contextual and situational which imply that Adjacency Pairs emerge in different structures within different contexts of conversations.          Keywords: Adjacency pairs, turn taking, conversation, speech act, utterance PASANGAN BERDAMPINGAN PADA UJARAN PERCAKAPAN DI NASKAH FILM LOST IN TRANSLATION KARYA SOFIA COPPOLAAbstrakArtikel ini berisi pembahasan tentang pola Pasangan Berdampingan berdasarkan ujaran percakapan pada naskah filem Lost in Translation melalui teori analisis percakapan. Percakapan terdiri atas dua giliran and ujaran yang mengandung dua tindak tutur. Ujaran-ujaran yang terdiri atas bagian berdampingan pertama dan diikuti bagian berdampingan kedua sehingga membentuk pasangan berdampingan baik dengan respon yang diharapkan maupun yang tidak diharapkan. Pasangan Berdampingan khususnya respon yang diharapkan terdiri atas dua puluh delapan pola berdampingan, sedangkan respon yang tidak diharapkan terdiri atas empat belas pola. Ragam respon dapat dipengaruhi oleh kebiasaan dan budaya pembicara pada saat berbicara. Perbedaan kebiasaan dan budaya mempengaruhi pembicara dalam membuat ujaran yang mengandung tindak tutur tertentu. Subjektifitas dan intensi juga dapat mempengaruhi respon pembicara kedua terhadap tindak tutur pembicara pertama. Hal ini bersifat subjektif namun bukan tidak logis. Pola yang komplels pada Pasangan Berdampingan juga dapat dipengaruhi oleh suasana ribut, suara yang kurang jelas, dan struktur kalimat yang kompleks. Ragam pola tersebut pada dasarnya bersifat kontekstual dan situasional yang berarti bahwa pola Pasangan Berdampingan akan berbeda pada konteks percakapan yang berbeda.   Kata kunci: Pasangan berdampingan, giliran berbicara, konversasi, tindak tutur, ujaran